The Cost of Care Associated with Microvascular Free Tissue Transfer by Anatomical Region: A Time-Driven Activity-Based Model - Lindell, Jackson S.; Blaschke, Breanna L.; Only, Arthur J.; Parikh, Harsh R.; Gorman, Tiffany L.; Vang, Sandy X.; Mahajan, Ashish Y.; Cunningham, Brian P. (Journal of Reconstructive Microsurgery Open, 2021)
Background Microvascular free tissue transfer (FTT) is a reliable method for reconstruction of complex soft tissue defects. The goal of this study was to utilize time-driven activity-based cost (TDABC) accounting to measure the total cost of care of FTT and identify modifiable cost drivers.Methods A retrospective review was performed on patients requiring FTT at a single, level-I academic trauma center from 2013 to 2019. Patient and surgical characteristics were collected, and six prospective FTT cases were observed via TDABC to collect direct and indirect costs of care.Results When stratified by postoperative stay at intensive care units (ICUs), the average cost of care was $21,840.22, while cases without ICU stay averaged $6,646.61. The most costly category was ICU stay, averaging $8,310.99 (40.9% of nonstratified overall cost). Indirect costs were the second most costly category, averaging $4,388.07 (21.6% of nonstratified overall cost). Overall, 13 of 100 reviewed cases required some form of revision free-flap, increasing cumulative costs to $7,961.34 for cases with non-ICU stay and $22,233.85 for cases with ICU stay, averaging up to $44,074.07 for patients who stayed in the ICU for both procedures. An increase in cumulative cost was also observed within the timeframe of the investigation, with average costs of $8,484.00 in 2013 compared to $45,128 for 2019.Conclusion Primary drivers for cost in this study were ICU stay and revision/reoperation. Better understanding the cost of FTT allows for cost reduction through the development of new protocols that drive intraoperative efficiency, reduce ICU stays, and optimize outcomes.
Keywords: free tissue transfer (FTT); time-driven activity-based cost (TDABC); indirect costs; direct costs